Exposure of individual harbour seals (Phoca vitulina) and waters surrounding protected habitats to acoustic deterrent noise from aquaculture. Issue 5 (15th March 2022) - Findlay, Charlotte R.; Hastie, Gordon D.; Farcas, Adrian; Merchant, Nathan D.; Risch, Denise; Wilson, Ben
Abstract: Pinniped depredation at aquaculture sites is a globally recognized problem. To mitigate depredation, the aquaculture sector uses acoustic deterrent devices (ADDs) as a non‐lethal alternative to shooting pinnipeds interacting with caged finfish. However, it is unclear whether sound emissions from ADDs have the potential to also impact non‐target pinnipeds at spatial scales relevant to populations. Global Positioning System (GPS) tracking data from seven harbour seals tagged in a non‐aquaculture context, on the west coast of Scotland, in 2017 were combined with modelled maps of ADD noise to quantify sound exposure and estimate the potential for auditory impairment. The acoustic model applied an energy flux approach across the main frequency range of ADDs (2–40 kHz). Predictions of temporary and permanent auditory threshold shifts were made using seal location data and published noise exposure criteria. The acoustic exposure of waters (10‐km buffers) surrounding protected habitats (i.e. designated haul outs and Special Areas of Conservation (SACs)) on the west coast of Scotland was also assessed. All tagged seals and waters surrounding 51 of 56 protected sites were predicted to be exposed to ADD noise exceeding median ambient sound levels. Temporary auditory impairment was predicted to occur in one of the seven tagged harbour seals and across 1.7% of waters surrounding protected habitats over a 24‐hour period, when assuming a 100% ADD duty cycle. Although the predicted risk of auditory impairment appears to be relatively low, these findings suggest that harbour seals inhabiting inshore waters off western Scotland are routinely exposed to ADD noise that exceeds median ambient sound levels. This chronic exposure risks negative consequences for individual harbour seals among the wider population in this region. The use of ADDs to mitigate pinniped depredation should be carefully considered to reduce unintended habitat‐wide impacts on non‐target species, including pinnipeds that are not specifically interacting with aquaculture.